CONSTITUTIONAL EDUCATION IN FACING THE CHALLENGES OF GLOBALIZATION - Susianto, Susianto; Nurita, Riski Febria; Sunarjo, Sunarjo (Four Son Scholarship, 2024)
This research focuses on Progress technology has bring change big in life society , including in matter implementation constitution. One of the challenges that arise is potential the occurrence violation right basic human in the field technology information . Technology information can used For spread misinformation , speech hatred , and propaganda. In addition , technology information can also be used For do crime cyber , such as data theft , hacking , and online fraud . Other challenges that arise is existence digital divide . This is can cause discrimination and marginalization to groups prone to. Globalization presents both opportunities and challenges that require societies to adapt while preserving their core values and principles. Constitutional education plays a pivotal role in preparing individuals to navigate these changes effectively. This study explores the significance of constitutional education in addressing the challenges posed by globalization. It highlights how an understanding of constitutional principles fosters critical thinking, promotes active citizenship, and strengthens democratic values in a globalized world. Through a qualitative approach, this research examines the relationship between constitutional education and the development of a well-informed and socially responsible citizenry capable of addressing global issues without compromising national identity. The findings emphasize the need for integrating constitutional education into curricula to equip individuals with the knowledge and skills necessary to balance global integration with local governance and cultural preservation. By enhancing constitutional literacy, societies can build resilience against the disruptive forces of globalization while contributing to sustainable and inclusive development